A nationwide survey of fatigue in cancer patients in Taiwan: an unmet need. (18th April 2020) - Rau, Kun-Ming; Shun, Shiow-Ching; Chiou, Tzeon-Jye; Lu, Chang-Hsien; Ko, Wei-Hsu; Lee, Ming-Yang; Huang, Wen-Tsung; Yeh, Kun-Huei; Chang, Cheng-Shyong; Hsieh, Ruey-Kuen
Abstract: Background: Cancer-related fatigue (CRF) is an emerging clinical issue, although its prevalence and impact on quality of life (QOL) in cancer patients in Taiwan remain unclear. The present nationwide cross-sectional study was conducted to provide a thorough overview of the prevalence, related factors and impact of CRF in Taiwan. Methods: In this multi-center survey, data were collected using the International Classification of Diseases 10 th Revision (ICD-10) Fatigue evaluation, Brief Fatigue Inventory–Taiwan (BFI-T), the Chinese version of the Symptom Distressed Scale and a fatigue experience survey. Logistic regression was used to determine the correlations between fatigue characteristics and the factors studied. Results: A total of 1207 cancer patients were recruited from 23 hospitals in Taiwan. Fatigue was the most distressing symptom in Taiwanese cancer patients. The distress score was higher if CRF was diagnosed using ICD-10 compared with BFI-T. Rest and nutritional supplementation were the most common non-pharmacological treatments; blood transfusion was the most common pharmacological treatment. There were 45% of patients reported not receiving a timely intervention for fatigue. Conclusions: Fatigue is the most bothersome symptom reported by Taiwanese cancer patients. Caregivers should be aware of the impact of CRF on QOL in cancer patients, constantly measure the severity of fatigue and provide appropriate interventions. Abstract : Depending on the questionnaire used, the prevalence of fatigue in cancer patients in Taiwan ranges from 23.4 to 71.9%. Fatigue is the most bothersome symptom reported by cancer patients.